Development of a Hyaluronic Acid-Based Nanocarrier Incorporating Doxorubicin and Cisplatin as a pH-Sensitive and CD44-Targeted Anti-Breast Cancer Drug Delivery System - Yu, Tao; Li, Yongshuang; Gu, Xueyuan; Li, Qin (Frontiers in Pharmacology, 2020)
Tumor-targeting nanomaterial-based chemotherapeutic drug delivery systems have been shown to represent an efficacious approach for the treatment of cancer because of their stability in blood circulation and predictable delivery patterns, enhanced tumor-selective drug accumulation, and decreased toxicity to normal tissues. The cell-surface transmembrane glycoprotein CD44 binds to the extracellular domain of hyaluronic acid (HA), and is overexpressed in breast, ovarian, lung, and stomach cancer. In this study, an HA-based nano-carrier incorporating doxorubicin (DOX) and cisplatin (CDDP) was synthesized as a CD44-targeting anti-cancer drug delivery system, and its tumor inhibition effects against CD44+ breast cancer cells were evaluated in vitro and in vivo. These dual drug-loaded HA micelles (HA-DOX-CDDP) exhibited significantly enhanced drug release under acidic conditions, and showed higher cellular uptake and stronger cellular growth inhibition than free drugs against 4T1 (CD44+) breast cancer cells. In contrast, no significant differences in growth inhibition and cellular uptake were observed between HA-DOX-CDDP and free drugs in NIH-3T3 (CD44-) control cells. Furthermore, HA-DOX-CDDP micelles exhibited stronger inhibitory effects and lower systemic toxicity than free drugs in a 4T1 mammary cancer-bearing mouse model, as determined using immunofluorescence and histological analyses. Therefore, HA-DOX-CDDP micelles represent a promising drug delivery system that exhibits acid-sensitive drug release, CD44-targeted delivery, and excellent biocompatibility and biodegradation. These properties resulted in excellent tumor accumulation and reduced adverse effects, indicating that HA-DOX-CDDP micelles have promising potential applications in chemotherapy for breast cancer.